Estimating high‐risk cannabis and opiate use in Ankara, Istanbul and Izmir. (27th June 2016) - Kraus, Ludwig; Hay, Gordon; Richardson, Clive; Yargic, Ilhan; Ilhan, Mustafa Necmi; Ay, Pinar; Karasahin, Füsun; Pinarci, Mustafa; Tuncoglu, Tolga; Piontek, Daniela; Schulte, Bernd
Abstract: Introduction and Aims: Information on high‐risk drug use in Turkey, particularly at the regional level, is lacking. The present analysis aims at estimating high‐risk cannabis use (HRCU) and high‐risk opiate use (HROU) in the cities of Ankara, Istanbul and Izmir. Design and Methods: Capture–recapture and multiplier methods were applied based on treatment and police data stratified by age and gender in the years 2009 and 2010. Case definitions refer to ICD‐10 cannabis (F.12) and opiate (F.11) disorder diagnoses from outpatient and inpatient treatment records and illegal possession of these drugs as recorded by the police. Results: High‐risk cannabis use was estimated at 28 500 (8.5 per 1000; 95% confidence interval 7.3–10.3) and 33 400 (11.9 per 1000; 95% confidence interval 10.7–13.5) in Ankara and Izmir, respectively. Using multipliers based on capture–recapture estimates for Izmir, HRCU in Istanbul was estimated up to 166 000 (18.0 per 1000; range: 2.8–18.0). Capture–recapture estimates of HROU resulted in 4800 (1.4 per 1000; 95% confidence interval 0.9–1.9) in Ankara and multipliers based on these gave estimates up to 20 000 (2.2 per 1000; range: 0.9‐2.2) in Istanbul. HROU in Izmir was not estimated due to the low absolute numbers of opiate users. Discussion and Conclusions: While HRCU prevalence in both Ankara and Izmir was considerably lower in comparison to an estimate for Berlin, the rate for Istanbul was only slightly lower. Compared with the majority of European cities, HROU in these three Turkish cities may be considered rather low. [Kraus L, Hay G, Richardson C, Yargic I, Ilhan N M, Ay P, Karasahin F, Pinarci M, Tuncoglu T, Piontek D, Schulte B Estimating high‐risk cannabis and opiate use in Ankara, Istanbul and Izmir Drug Alcohol Rev 2016;00:000‐000]